Reversible Oxygenation of α-Amino Acid–Cobalt(II) Complexes - Xincun Zhang; Fan Yue; Hui Li; Yan Huang; Yi Zhang; Hongmei Wen; Jide Wang (Bioinorganic Chemistry and Applications)
We systematically investigated the reversibility, time lapse, and oxygenation-deoxygenation properties of 15 natural α-amino acid–Co(II) complexes through UV-vis spectrophotometer, polarographic oxygen electrode, and DFT calculations, respectively, to explore the relationship between the coordinating structure and reversible oxygenation of α-amino acid–Co(II) complexes. Results revealed that the α-amino acid structure plays a key role in the reversible oxygenation properties of these complexes. The specific configuration of the α-amino acid group affects the eg1 electron of Co(II) transfer to the π⁎ orbit of O2; this phenomenon also favors the reversible formation and dissociation of Co–O2 bond when O2 coordinates with Co(II) complexes. Therefore, the co-coordination of amino and carboxyl groups is a determinant of Co complexes to absorb O2 reversibly. The group adjacent to the α-amino acid unit evidently influences the dioxygen affinity and antioxidation ability of the complexes. The presence of amino (or imino) and hydroxy groups adjacent to the α-amino acid group increases the oxygenation-deoxygenation rate and the number of reversible cycles. Our findings demonstrate a new mechanism to develop reversible oxygenation complexes and to reveal the oxygenation of oxygen carriers.